Immune mapping of human tuberculosis and sarcoidosis lung granulomas - Carow, Berit; Muliadi, Victoria; Skålén, Kristina; Yokota, Chika; Kathamuthu, Gokul Raj; Setiabudiawan, Todia Pediatama; Lange, Christoph; Scheu, Katrin; Gaede, Karoline I.; Goldmann, Torsten; Pandita, Ankur; Masood, Kiran Iqbal; et al. (Frontiers in Immunology, 2024)
Tuberculosis (TB) and sarcoidosis are both granulomatous diseases. Here we compared the immunological micro-environments of granulomas from TB and sarcoidosis patients using in situ sequencing (ISS) transcriptomic analysis and multiplexed immunolabelling of tissue sections. TB lesions consisted of large necrotic and cellular granulomas, while "multifocal" granulomas with macrophages or epitheloid cell core and a T cell rim were observed in sarcoidosis samples. The necrotic core in TB lesions was surrounded by macrophages and encircled by a dense T cell layer. Within the T cell layer, compact B cell aggregates were observed in most TB samples. These B cell clusters were vascularized and could contain defined B/ T cell and macrophage-rich areas. The ISS of 40-60 immune transcripts revealed the enriched expression of transcripts involved in homing or migration to lymph nodes, that formed networks at single-cell distances in lymphoid areas of the TB lesions. Instead, myeloid annotated regions were enriched in CD68, CD14, ITGAM, ITGAX and CD4 mRNA. CXCL8 and IL1B mRNA were observed in granulocytic areas in which M. tuberculosis was also detected. In line with ISS data indicating tertiary lymphoid structures, immune labelling of TB sections expressed markers of high endothelial venules, follicular dendritic cells, follicular helper T cells and lymph-node homing receptors on T cells. Neither ISS nor immunolabelling showed evidence of tertiary lymphoid aggregates in sarcoidosis samples. Together, our finding suggests that despite their heterogeneity, the formation of tertiary immune structures is a common feature in granulomas from TB patients.